Pengaruh Sistem Informasi Manajemen Terhadap Kinerja Karyawan Di PT. Ecogreen Oleochemicals Batam - Desi Sariani (Computer Based Information System Journal, 2014)
By looking at the influences on the development of management information systems employee performance improvement with the information systems used in PT. Ecogreen Oleochemicals Batam. And to identify the variables in a more comprehensive and see how much influence the system variable management information on the performance of employees. The purpose of this study was to obtain an overview of Management Information Systems at PT. Ecogreen Oleochemicals Batam, to obtain an overview of the performance of employees at PT. Ecogreen Oleochemicals Batam, to gain influence on the performance of Management Information Systems employees at PT. Ecogreen Oleochemicals Batam. Management Information Systems required six components of information, human as an information processor, system concept, the concept of organization and management, the concept of decision-making, values ​​and information to support employees' performance, namely: the ability, initiative, punctuality, quality of work, research communication. Method used is descriptive research method, Verikatif with a quantitative approach that is research is research that uses numerical data (numbers), which is then processed and analyzed to be taken conclusion. So that results obtained from this study is the management information system significantly influence performance of employees at PT. Ecogreen Oleochemicals Batam.